The man-propelled aircraft: a preliminary assessment - Nonweiler, T. (College of Aeronautics, 1956)
1. Introduction It is the intention of this note to set down a few tentative, but (it is hoped) realistic, assessments of the problems involved in the design of an aircraft which by the crew's own muscular efforts shall take off from the ground and sustain steady flight, for a short period. The desire to fly is one of the oldest dreams of mankind, and it has of course found partial fulfilment with the help of external sources of power : but the ultimate achievement of unaided flight is yet to be realised. Everest was "conquered" with the help of the internal combustion engine in 1933 ; but the ultimate achievement was the greater glory of 1954. If the conclusions of this paper are correct, man-powered flight can surely be another "crowning glory" very soon. These conclusions may of course be incorrect; the amount of work done hardly justifies unqualified confidence in their truth. Yet a useful purpose will be served by this note if it causes sufficient enthusiasm or distrust to stimulate researches by those better qualified than the author to dogmatise on many of the aspects of the problem treated...[cont.].